2015
DOI: 10.1186/s12886-015-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative intraocular pressure does not influence outcome of trabeculectomy surgery: a retrospective cohort study

Abstract: BackgroundTo investigate whether pre-operative intraocular pressure (IOP) predicts outcome of trabeculectomy surgery in patients with primary open angle glaucoma over a 3-year period of follow-up.MethodsRetrospective cohort study, of a total of 61 patients (80 procedures) who had undergone trabeculectomy surgery after failed medical management at a single centre between 2000 and 2011. Patients were identified through surgical logbooks. A subsequent case note-review identified 61 patients (80 procedures) with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This is consistent with the findings of a study on POAG patients where they found that preoperative IOP did not predict the success of trabeculectomy or the incidence of surgical complications and low preoperative IOP did not increase the need for postoperative interventions. 15 However Jampel et al 16 found lower preoperative IOP to be associated with trabeculectomy failure. We found no difference between the two groups with regards to the percentage of patients achieving complete and partial success as demonstrated in the Kaplan-Meier curves.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of a study on POAG patients where they found that preoperative IOP did not predict the success of trabeculectomy or the incidence of surgical complications and low preoperative IOP did not increase the need for postoperative interventions. 15 However Jampel et al 16 found lower preoperative IOP to be associated with trabeculectomy failure. We found no difference between the two groups with regards to the percentage of patients achieving complete and partial success as demonstrated in the Kaplan-Meier curves.…”
Section: Discussionmentioning
confidence: 99%
“…There may be some factors which can influence the final success of trabeculectomy. [ 8 9 ] The main factor may be the inflammatory response of the eye to the surgery, which may be influenced by surgical trauma and/or previous medication or previous inflammation. While Ayala et al .…”
Section: Introductionmentioning
confidence: 99%
“…Laser trabeculoplasty is used to increase the outflow of aqueous humor 19 . Another surgical therapy, called trabeculectomy, creates an alternative drainage site to filter AH when the traditional trabecular pathway is blocked [20][21] . These treatment options have been known to effectively reduce IOP.…”
Section: Introductionmentioning
confidence: 99%